Ultra High-Performance Supercritical Fluid Chromatography for the Quantitation of Diterpene Resin Acids in Norway Spruce Samples - Goels, Thomas; Eichenauer, Elisabeth; Langeder, Julia; Aichner, Georg F.; Mauser, Gregor; Amtmann, Luisa; Grienke, Ulrike; Glasl, Sabine (Frontiers in Pharmacology, 2022)
Picea abies (L.) H. Karst. (Pinaceae) is native to Northern, Central and Eastern Europe. The fast-growing tree reaches up to 50 m in height, has modest nutritional requirements and depends on sufficient water supply. Norway spruce produces exudates which are traditionally used to treat skin wounds. Major bioactive constituents of the conifer oleoresin are diterpene resin acids (DRAs) of the abietane and the pimarane type. To assure consistent pharmaceutical quality of Norway spruce balm and commercial products thereof, an analytical method for the quantitation of DRAs is the prerequisite. However, high structural similarity among DRAs and their poor UV absorption makes chromatographic separation and detection challenging: Conventional liquid chromatography systems often fail to achieve sufficient separation and are not sustainable. Gas chromatography requires time-consuming derivatization prior to unacceptably long analyses (> 60 min). These drawbacks prompted the development of the first validated supercritical fluid-based protocol for the separation and quantitation of eight DRAs, i.e. pimaric acid (1), sandaracopimaric acid (2), palustric acid (3), isopimaric acid (4), levopimaric acid (5), abietic acid (6), dehydroabietic acid (7), and neoabietic acid (8). By using an ultra high-performance supercritical fluid chromatography (UHPSFC) device hyphenated to a quadrupole mass detector, the DRAs were separated in less than 20 minutes on a Torus 2-Picolylamin (2-PIC) column (3.0 mm × 100 mm; 1.7 µm particle size) applying supercritical CO2 and ethanol as mobile phase. Regarding selectivity, accuracy (recovery rates: 87-108%), intermediate precision (between 6.6-11.1%), and linearity (R2 ≥ 0.99; linear between 0.75 µg/ml and 2.5 mg/ml), results were obtained in line with ICH guidelines. The lowest limit of detection (LOD) was at 0.75 µg/ml (7) and the lowest limit of quantitation (LOQ) at 2 µg/ml (8). As application examples, 22 Norway spruce balm samples and five commercial products were analyzed. The presented protocol not only simplifies and shortens the analytical workflow, but also reduces the amount of organic solvent waste by about two thirds compared to conventional liquid chromatographic set-ups. These advantages qualify this fast and efficient method as an ideal tool for an environmentally friendly quality control of traditionally used wound-healing Norway spruce balm products.